Power Quality Enhancement with Involvement of RES and Power Converters in Micro Grids using Metaheuristic Algorithms: A Literature Review - Srikanth, T.; Kannan, A. S.; Chandra, B. M. (Asian Journal of Electrical Sciences, 2020)
Micro Grids are going to replace the traditional concept of electrical networks in order to satisfy the increasing needs in terms of flexibility, accessibility, reliability, and quality of the power supply. Economy and energy efficiency are the paradigms followed to exploit the available distributed energy resources (DERs), guaranteeing technical and environment-friendly standards. Obviously, the path to Micro Grids is complicated by the increasing heterogeneity of Micro Grid components, such as renewable, storage systems, fossil- fueled generators, and controllable loads [1]. Fortunately, the synergic interaction between DERs and information and communication technologies (ICT) foster the coordination among different infrastructures, promoting the development of Smart Grids at both theoretical and practical levels. The major highlights of utilizing micro grid are the capacity to self-heal from power quality (PQ) issues, efficient energy management, incorporation of automation based on ICT and smart metering, integration of distributed power generation, renewable energy resources, and storage units [2]. The advantages contribute to maintain good PQ and to maintain the reliability. In this regard, the concept of micro grid is brought to the stage as one of the main building blocks of the future smart grids [3].